Measurement of the W boson helicity in top quark decays using 5.4fb -1 of pp̄ collision data - Abazov, V. M. (2011)
We present a measurement of the helicity of the W boson produced in top quark decays using tt̄ decays in the l+jets and dilepton final states selected from a sample of 5.4fb-1 of collisions recorded using the D0 detector at the Fermilab Tevatron pp̄ collider. We measure the fractions of longitudinal and right-handed W bosons to be f0=0.669±0. 102[±0.078(stat.)±0.065(syst.)] and f+=0.023±0. 053[±0.041(stat.)±0.034(syst.)], respectively. This result is consistent at the 98% level with the standard model. A measurement with f 0 fixed to the value from the standard model yields f +=0.010±0.037[±0.022(stat.)±0.030(syst.).]. © 2011 American Physical Society.